Magia niepozornych rzeczy w twórczości Justyny Bednarek - Chrobak, Małgorzata Ewa (Paidia i Literatura, 2022)
Małgorzata Ewa Chrobak’s aim in this article is to read Justyna Bednarek’s books for children from the perspective of “thing studies.” Chrobak investigates how everyday objects and their re-use are represented in a selection of those books, e.g., Nowe przygody skarpetek (jeszcze bardziej niesamowite) [The Socks’ New Adventures (More Amazing Than Ever)]; Banda Czarnej Frotté [The Band of the Black Frotté]; Skarpetki powracają! [The Socks Are Back!]; Zielone piórko Zbigniewa [Zbigniew’s Green Feather]; Skarpetki kontratakują! [The Socks Strike Back!]. Chrobak examines the possibilities of applying two interpretive categories to Bednarek’s fiction, those of “biography of things” and “cultural recycling.”